Evaluation of Maternal and Fetal Stress Hormones During the Process of Birth - Burcu Kisa Karakaya; Ozlem Moraloglu; Rahime Bedir Findik; Necati Hancerliogullari; Hatice Celik; Tuba Candar; Halil İbrahim Yakut (Gynecology Obstetrics & Reproductive Medicine, 2018)
Objective: This study aims to determine whether mode of delivery is associated with the endocrine stress response in mother and newborn.